Kesempatan Kerja Bagi Masyarakat Dengan Adanya Bali safari and Marine park Di desa Serongga, Kabupaten Gianyar - Gunawan, Bernardinus Ignasius; Adikampana, I Made (JURNAL DESTINASI PARIWISATA, 2019)
This paper, entitled "employment opportunities for people with the Bali Safari And Marine Park in Serongga Village, Gianyar Regency." The importance of the research carried out is to know the influence of the existence of the Bali Safari And Marine Park (BSMP) towards employment opportunities obtained village community Serongga. Data analysis technique used is descriptive-qualitative techniques, namely how the excavation information then the results are depicted in the form of words or sentences then its compilation is done systematically and accurately about the fact are there so that the result is related to the development of tourism and its influence on the employment opportunities available to the community of the village of Serongga. Based on research results, employment opportunities obtained by the Serongga village community by having BSMP divided into two i.e. employment opportunities directly and indirectly. Immediate job opportunities divided into employment as labor contracts and as workers in art BSMP. Indirect job opportunities divided into employment opportunities as a livestock feed suppliers in the form of elephant grass and fresh vegetables as well as employment opportunities as a provider of food for the staff at BSMP   Keywords : employment, community, existence.